PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL, PARTISIPASI ORANG TUA, DAN MOTIVASI BELAJAR DI MASA PANDEMI COVID-19 TERHADAP PRESTASI BELAJAR - Muhammad Fajar Kurniawan; Sutiah Sutiah; Endah K Purwaningtyas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The way of learning that is carried out in the education system in Indonesia is to use the classical system or be done face-to-face directly. Conditions in the current state of the COVID-19 pandemic emergency, everyone must do online learning, including in elementary schools. In online learning, students can become less dynamic in conveying goals and thoughts, which can lead to tiring learning. A student who experiences boredom in learning will get progress in learning outcomes. So that teachers use alternatives to support the learning process by using audio-visual media, parental participation and learning motivation. The objectives to be achieved are: To determine the effect of using audio-visual media, parental participation, and learning motivation during the covid-19 pandemic on achievement studying in school. This research method uses a quantitative approach used in this study, namely the quantitative correlational approach. To collect samples using the Problem Examination procedure with a kind of regular randomized examination strategy (Methodical Irregular Examining), with a population of 160, a sample of 32 was obtained. mean scores 3.94, 3.91, and 3.94. 2. Parental participation directly affects the learning achievement of school students in Singkut sub-district with a score of 6.013> 2.048. This means that there is a significant effect between the variables of Parental Participation on learning achievement. 3. The variables using Audio Visual Media, Parental Participation, and Learning Motivation have a value of 57.8% affecting learning achievement obtained from the value of the effective contribution of each variable used in the study, the other 42.2% is influenced by other variables that are not used in research..